(untitled) (Geography and Tourism, 2017)
The paper presents different variants for a Bydgoszcz bypass canal prepared based on the analysis of historical materials as well as contemporary environmental and economic factors. While preparing the concept, the following aspects were taken into account: land relief, current land-use patterns, nature protection forms, and inland waterway development plans, including the location of a multimodal port in the vicinity of Solec Kujawski. As a result of the conducted analysis, four variants of the bypass canal were established: two of them running north of and two south of Bydgoszcz. In addition, their environmental and infrastructural impact was preliminary assessed as well as their functional and spatial connections with the surroundings were analysed. Furthermore, measures aimed at executing the designed projects were suggested.